PENGARUH PENGGUNAAN TEKNOLOGI CRF (Controlled Release Fertilizer) PADA UJI EFEKTIVITAS TANAMAN BAWANG MERAH - Finalis, Era Restu; Noor, Ilhamsyah; Arfiana, Arfiana; Tjahjono, Endro W.; Mulyono, Agus; Suratno, Hadi (Department of Agroindustrial Technology, Bogor Agricultural University, 2024)
Shallot (Allium cepa L. var ascalonicum) is one of the leading vegetable commodities that is widely used and has high economic value. National shallot productivity continues to decline from year to year, so it is necessary to increase shallot production both in quantity and quality. One way that can be done is to apply effective efforts in the cultivation system such as the use of effective and efficient fertilizer technology. The purpose of this research was to determine the effect of using Controlled Release Fertilizer (CRF) technology on the effectiveness test of the shallot variety SS Sakato which was carried out on a 4200 m2 plot of land in Kuningan, West Java. The results show that the use of CRF technology can increase growth (plant height), and the number of tillers, and increase shallot productivity. The increase in plant height at 30 HST increased by an average of 50% for all treatments and then slowed down to 20% in the second month. Regarding the number of tillers, the use of CRF technology can increase by about 38% when compared to controlled plots. Against the weight of the harvest, it can increase by 7-22% higher than the use of NPK fertilizer (comparison). The quality of the shallots produced also shows better with larger tuber sizes and brighter colours. Keywords: Controlled Release Fertilizer (CRF), fertilizer, shallot, the effectiveness test, Sakato